2020
DOI: 10.1111/bph.15000
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine: A promising drug for the treatment of pulmonary hypertension

Abstract: Background and Purpose: Tetramethylpyrazine (TMP) was originally isolated from the traditional Chinese herb ligusticum and the fermented Japanese food natto and has since been synthesized. TMP has a long history of beneficial effects in the treatment of many cardiovascular diseases. Here we have evaluated the therapeutic effects of TMP on pulmonary hypertension (PH) in animal models and in patients with pulmonary arterial hypertension (PAH) or chronic thromboembolic pulmonary hypertension (CTEPH).Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 57 publications
(71 reference statements)
1
27
0
Order By: Relevance
“…Tetramethylpyrazine, extracted from the traditional herbal medicine Ligusticum , effectively prevents and reverses PAH in different animal models such as chronic hypoxia-induced PAH, sugen/hypoxia-induced PAH, and MCT-induced PAH in rodents ( Chen et al, 2020c ). In hypoxia-induced PAH, tetramethylpyrazine improved pulmonary vascular leakage and attenuated the elevation of ROS, HIF1α, and VEGF protein levels ( Zhang et al, 2011 ).…”
Section: Preclinical Studies Of Traditional Herbal Medicine For Pulmonary Arterial Hypertension Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetramethylpyrazine, extracted from the traditional herbal medicine Ligusticum , effectively prevents and reverses PAH in different animal models such as chronic hypoxia-induced PAH, sugen/hypoxia-induced PAH, and MCT-induced PAH in rodents ( Chen et al, 2020c ). In hypoxia-induced PAH, tetramethylpyrazine improved pulmonary vascular leakage and attenuated the elevation of ROS, HIF1α, and VEGF protein levels ( Zhang et al, 2011 ).…”
Section: Preclinical Studies Of Traditional Herbal Medicine For Pulmonary Arterial Hypertension Treatmentmentioning
confidence: 99%
“…Nowadays, the clinical trial of tetramethylpyrazine in PAH treatment is ongoing (registered with www.chictr.org.cn as ChiCTR-IPR-14005379). Therefore, tetramethylpyrazine has the potential to be a novel and inexpensive medication for PAH ( Chen et al, 2020c ).…”
Section: Preclinical Studies Of Traditional Herbal Medicine For Pulmonary Arterial Hypertension Treatmentmentioning
confidence: 99%
“…Multiple studies showed that activators of K + channels [ 7 , 99 ] and inhibitors of both Cl - channels [ 98 ] and TRPC channels [ 100 ] can prevent and/or reverse PAH in animal models. Optimising the selectivity, potency and lung-specific delivery of these compounds will therefore be paramount to the development of new PAH therapies.…”
Section: Summary and Implications For Therapymentioning
confidence: 99%
“…We recently documented that the combination of RAS and RLC effectively ameliorated fibrotic liver injury by decreasing BA accumulation and repressing the production of inflammatory cytokines [ 16 ]. Bioactive ingredients of RPA and RRP exhibited hepatoprotective effects as well [ 17 ]. However, the underlying mechanism of SWT in treating fibrotic liver injury remains elusive yet and demands urgent clarification.…”
Section: Introductionmentioning
confidence: 99%